Thermal-Economic Analysis of an Organic Rankine Cycle System with Direct Evaporative Condenser - Yu, Xiaohui; Geng, Jiabao; Gao, Zhi (Journal of Advanced Thermal Science Research, 2023)
The organic Rankine cycle (ORC) system for power generation has proven to be an effective technology for low-temperature waste heat utilization. Accurate prediction and comprehensive comparison of system performance under different conditions are necessary for the development and application of suitable ORC configurations. This paper proposed an organic Rankine cycle (ORC) system using a direct evaporative condenser to realize performance enhancement and analyzed its dynamic performance based on the actual climatic condition, which is beneficial for the performance optimization of this system. This study begins with an introduction to the thermal economics model of the proposed system and evaluates the performance of the system based on the 3E (energy, exergy, economy) analysis method. Secondly, four candidate working fluids were compared and analyzed, leading to the selection of R142b as the best working fluid for the proposed system. Finally, the dynamic performance of the proposed system using the working fluid of R142b was analyzed based on the hourly environment temperature. The result showed that the net thermos-electric conversion efficiency of the system was negatively correlated with the ambient wet-bulb temperature. The annual average exergy efficiency of the system is about 65.79%, and the average exergy loss of the heat absorption unit, evaporative condenser, pump, and expander account for 61.07%, 6.92%, 2.99%, and 29.01% of the exergy loss of the system respectively. In the case 8760 h of operation per year, the payback period of the proposed ORC system using direct evaporative condenser is about 2.14 years.